Komparasi Sifat Kimia Hara Makro pada Lahan yang Akan Ditanami Padi (Oryza sativa L.) di Kabupaten Garut - Swardana, Ardli; Mutakin, Jenal; Asfianti, Asti; Muhidin, Rahmat; Hilma, Ai; Aminudin, Arif; Mahendra, Rafly (JAGROS : Jurnal Agroteknologi dan Sains (Journal of Agrotechnology Science), 2025)
Rice is an important food crop whose cultivation activities are carried out continuously throughout the year. Rice cultivation activities require soil fertility tests, such as the presence of chemical properties of macronutrients that plants need in large quantities than other nutrients for fertilization efficiency and saving fertilizer resources. The purpose of the study was to compare macronutrients in several locations in Garut Regency that would be planted with rice. The study was conducted in 3 districts, namely Tarogong Kidul, Wanaraja, and Banyuresmi, Garut Regency in August 2024 - January 2025. The data collection method was carried out by sampling at 3 research locations, while data analysis used a descriptive quantitative-qualitative method from the results of laboratory measurements categorized based on the 1983 Soil Research Center. The results showed that the nitrogen and potassium values ​​in the three locations had the same category, namely low for nitrogen nutrients and very high for potassium nutrients. Phosphorus nutrients have a more diverse category compared to nitrogen and potassium, namely from low to moderate.